PERANCANGAN TATA LETAK FASILITAS MENGGUNAKAN METODE ARC DAN BLOCKPLAN PADA PT. MMP - Alfin, Alfin_Kurnia_Setiawan; Abrar Zaki Abirama Fawwaz; Muhammad Qiyanul Fikri; Yudhistira Daffa Pramudya; Dominicus Alferdo Rivaldi; Andung Jati Nugroho (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to redesign the production facility layout at PT. MMP in order to improve material flow efficiency and reduce material handling costs. The methods applied in this research are Activity Relationship Chart (ARC), From-To Chart (FTC), and Blocplan. Data were collected through direct observation, interviews, and documentation related to production processes, inter-department distances, and material movement frequencies. The results indicate that the existing layout is inefficient due to long material transfer distances. By redesigning the layout using the Blocplan method, a more optimal facility arrangement was obtained with reduced travel distances and improved production flow. The material handling cost analysis shows a decrease from Rp177,000 in the ARC layout to Rp64,000 in the Blocplan layout. Therefore, the Blocplan method is proven to be more effective in improving facility layout efficiency and reducing operational costs.